Multi-scale modelling of discontinuous carbon fibre reinforced composites - Bond, Michael David (2013)
Discontinuous carbon fibre composites are becoming increasingly popular in the automotive and aerospace sectors, as an alternative to textile-based fibre reinforced composites for both semi-structural and structural components. Materials are highly heterogeneous, with the random architecture leading to uncertainties when modelling and predicting mechanical performance. The microscopic characteristics are known to dominate the strength of the composite, which need to be correctly represented to improve mechanical property predictions at the macroscale.